Building Organizational Resilience in Creative Fashion SMEs: A Literature Review - ‎ , Zahro; Affa, Ahmad Syaiful; Adriyana, Rika; Mahmudah, Dina Amalia; Khasanah, Eka Siti (KnE Social Sciences, 2024)
This literature review examines the process of building organizational resilience among small and medium-sized enterprises (SMEs) in the creative fashion industry, specifically within the context of the fashion batik sector in Pekalongan. The study identifies the challenges encountered by SMEs in this industry, including limited access to capital, technological barriers, intense competition, changing consumer preferences, and sustainability issues. To address these challenges, the review presents strategies and best practices for enhancing organizational resilience. These strategies include diversifying and strengthening financial resources, embracing technology and innovation, enhancing market positioning and branding, fostering collaborative networks, strengthening supply chain management, investing in human capital, embracing sustainable practices, and engaging with the local community and tourism sector. The review highlights the importance of a supportive ecosystem, which includes government support, industry associations, and educational institutions, in implementing these strategies effectively. By implementing these strategies, SMEs in the creative fashion industry can overcome challenges, enhance their resilience, and sustain long-term growth and success. The findings of this review provide a roadmap for SMEs in Pekalongan and similar contexts to navigate the competitive fashion batik industry and build resilience, contributing to the overall competitiveness and sustainability of the industry. Keywords: organisational resilience, SMEs, creative fashion industry, fashion batik, pekalongan